Robust and Accurate Positioning Control of Solar Panel System Tracking based Sun Position Image - Lailis Syafa'ah; Lailatul Fauziyah; Zulfatman Has (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
This study contains the robust and accurate positioning control design for solar panel system consisting of elevation and azimuth axis tracker. The ultimate objective of the study is to ensure the solar panel move accurately to follow its tracking reference against mechanical load and other disturbances. The tracking reference was the images of actual sun position. Image processing result as the initial reference and high precision encoder as the controller feedback path were intended to obtain the accurate position of hardware response. Sliding Mode Controller (SMC) with Proportional Integral Derivative (PID) Sliding Surface was employed as control technique that guarantee the solar panel system robust against disturbances or load variation. The proposed method was evaluated through software simulation and hardware validation. The software for the simulation and validation was LabVIEW. While the software for image processing was Vision Assistant. From hardware validation, accuracy of the solar panel system to track the sun position image for elevation and azimuth were 2.622% (0.03007 ) and 0.244% (0.00893 ), respectively. These results indicate that the solar panel system was available to move accurately to track the sun position both in azimuth and elevation axis.